Protective Effects and Active Ingredients of Yi-Qi-Fu-Mai Sterile Powder Against Myocardial Oxidative Damage in Mice - Yu-Qing Wang; Chun-Hua Liu; Jie-Qiong Zhang; Dan-Ni Zhu; Bo-Yang Yu (Elsevier, 2013)
Abstract.: This study aims to evaluate the protective effects of Yi-Qi-Fu-Mai sterile powder (YQFM) on myocardial oxidative damage and tries to identify the active components responsible for its pharmacological benefits. YQFM and the n-butanol extract of YQFM (YQFM-Bu) were administered to ISO-induced myocardial injury mice. Left ventricle weight index and histopathological analyses were conducted. Serum enzymatic activities of lactate dehydrogenase (LDH), creatine kinase (CK) and superoxide dismutase (SOD), myeloperoxidase (MPO), and the levels of malondialdehyde (MDA) were also measured. Our results demonstrated that both YQFM and YQFM-Bu significantly restored the abnormal activities of CK, LDH, MPO, SOD, and the levels of MDA in ISO-induced myocardial injury mice, and these biochemical results were further supported by histopathological data. Our in vitro findings also confirmed that both YQFM and YQFM-Bu exhibit significant radical scavenging activity. Furthermore, the major active fractions of YQFM were identified by UPLC-MS/MS. Twenty-five ginsenosides and three lignans were identified from YQFM-Bu. These findings suggested YQFM-Bu is the major active fraction of YQFM with the ginsenosides and lignans as potential active components responsible for its protective effect against myocardial injury, and YQFM exerted its beneficial effects on myocardial injury mainly through inhibiting oxidative damage and maintaining the functional integrity of myocardial tissue. Keywords:: myocardial oxidative damage, Traditional Chinese Medicine, Yi-Qi-Fu-Mai sterile powder, active ingredient, cardioprotection